English file. Elementary, Student's book - Latham-Koenig, Christina; Oxenden, Clive; Seligson, Paul (Oxford : Oxford University Press, 2012)
Each File presents and practises grammar, vocabulary and pronunciation with a balance of reading and listening activities and lots of opportunities for speaking Clear, colour-coded referencing to additional resources at the back of the Student's Book - such as Grammar Bank, Vocabulary Bank and Sound Bank - offer additional support A wide variety of authentic texts and dialogues provides fresh angles on topics which motivate students Practical English lessons teach useful high-frequency, everyday English and social English Revise & Check pages with 'Can you?' challenges helps students consolidate and measure their progress Real-world In-The-Street interviews, Practical English drama and documentary videos motivate and engage students with English language and culture Clear signposts to iTutor throughout the Student's Book encourage self-study The iTutor DVD-ROM contains all the Student's Book audio, video, grammar and vocabulary exercises in one place making it easy for students to catch-up, revise and study at home.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Problems, exercises, etc; English language -- Textbooks for foreign speakers